2004
DOI: 10.1093/nar/gkh128
|View full text |Cite
|
Sign up to set email alerts
|

AANT: the Amino Acid-Nucleotide Interaction Database

Abstract: We have created an Amino Acid-Nucleotide Interaction Database (AANT; http://aant.icmb.utexas. edu/) that categorizes all amino acid-nucleotide interactions from experimentally determined protein-nucleic acid structures, and provides users with a graphic interface for visualizing these interactions in aggregate. AANT accomplishes this by extracting individual amino acid-nucleotide interactions from structures in the Protein Data Bank, combining and superimposing these interactions into multiple structure files … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(96 citation statements)
references
References 25 publications
4
92
0
Order By: Relevance
“…For instance, some structural studies provided valuable information about the protein-DNA interactions, giving the description of the complementary surfaces involved, responsible for the topology recognition, and the chemistry of these surfaces that is the base of the chemical recognition (Luscombe et al, 2001;Hoffman et al, 2004). The structure of both proteins and nucleic acids can be diverse and the proteins may interact with the DNA molecule by exhibiting amino acids' residues able to interact specifically with particular DNA sequences.…”
Section: Cellular Protein-dna Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some structural studies provided valuable information about the protein-DNA interactions, giving the description of the complementary surfaces involved, responsible for the topology recognition, and the chemistry of these surfaces that is the base of the chemical recognition (Luscombe et al, 2001;Hoffman et al, 2004). The structure of both proteins and nucleic acids can be diverse and the proteins may interact with the DNA molecule by exhibiting amino acids' residues able to interact specifically with particular DNA sequences.…”
Section: Cellular Protein-dna Complexesmentioning
confidence: 99%
“…This database was later improved since overlapping structures could not be analysed and interactions involving the peptide backbone and sugarphosphate backbone were not included. Hoffman et al (2004) created the amino acid-nucleotide interaction database (AANT) that deconstructs 930 protein-nucleic acid structures into sets of amino acid nucleotide interactions, allowing to identify the residues that participate in multiple interactions with the nucleotides moieties, modulating new nucleic acid structures and placing sterically similar interactions and altering specificities. Nevertheless, the AANT only predicted hydrogen bonds.…”
Section: Protein-dna Interactionsmentioning
confidence: 99%
“…Furthermore, atomic studies performed on protein-RNA complex structures have shown that histidine has a strong tendency to interact with nucleotides (Jeong et al, 2003). As for the exact type of interactions, these may include (i) hydrogen-bonding between H-donor (NtH) and H-acceptor (Np) atoms in the non-protonated histidine with base edges; (ii) ring stacking/hydrophobic interactions and (iii) water-mediated hydrogen bonds (Hoffman et al, 2004;Morozova et al, 2006). Thus, and considering the fact that at the working pH (7.0), histidine (pK a ¼ 6.5) is not significantly protonated (Ö zkara et al, 2002;Pitiot and Vijayalakshmi, 2002) the elution of sRNA when salt concentration is decreased suggests that ring stacking/ hydrophobic interactions and histidine-RNA direct hydrogenbonding are the dominant effects.…”
Section: Chromatographic Separation Of Srna 6smentioning
confidence: 99%
“…6S RNA presents a DNA promoter-like secondary structure consisting of two long irregular double-stranded stem regions, which are interrupted by small bulge loops and a largely single-stranded internal loop in the central region. Along the central bulge and through the continuous stem sequences there are mostly adenines (A) and guanines (G) (Barrick et al, 2005), which were described to interact preferably with histidine (Hoffman et al, 2004). Interestingly, in newly described aspects on the function of 6S RNA, A and G were also identified as specific nucleotides involved in close contact with RNA polymerase (Gildehaus et al, 2007).…”
Section: Chromatographic Separation Of Srna 6smentioning
confidence: 99%
“…If so, then both types of nucleobases could play a significant role in DNA damage induced by lowenergy electrons. We inspected interactions published in an amino acid-nucleotide database (AANT) containing crystallographic structures for 1213 protein-nucleic acids complexes [84] and observed that the purine-amino acid side chains contacts account for the majority of interactions. Namely, out of 3066 contacts between nucleobases and amino acid side chains 43.7 and 21.4% fall to guanine and adenine, respectively.…”
Section: Interactions Of Dna With Proteins and Proton Transfer Inducementioning
confidence: 99%